Renewable Energy, Output, CO2 Emissions, and Fossil Fuel Prices in Central America: Evidence From a Nonlinear Panel Smooth Transition Vector Error Correction Model - Apergis, Nicholas; Payne, James (Elsevier, 2013)
This study examines the determinants of renewable energy consumption per capita for a panel of seven Central American countries over the period 1980 to 2010. Specifically, we find that a long-run cointegrated relationship exists between renewable energy consumption per capita, real GDP per capita, carbon emissions per capita, real coal prices, and real oil prices with the respective coefficients positive and statistically significant. A structural break in the cointegrating relationship appears in 2002 which coincides with the establishment of the Energy and Environment Partnership with Central America initiative to expand the use of renewable energy sources. Recognizing the regime shift in 2002, we estimate a nonlinear panel smooth transition vector error correction model to show that for the post-2002 period, the influence of renewable energy consumption per capita uponreal coal and oil prices strengthened relative to the pre-2002 period as well as a greater sensitivity of real GDP per capita to carbon emissions per capita.